Porcine Babesiosis Caused by Babesia sp. Suis in a Pot-Bellied Pig in South Africa - Avenant, Alida; Park, Janice Y.; Vorster, Ilse; Mitchell, Emily P.; Arenas-Gamboa, Angela M. (Frontiers in Veterinary Science, 2021)
Babesiosis is a worldwide, tick-borne disease of economic importance in livestock caused by Babesia spp., which are hemoparasitic piroplasms that target the host erythrocytes. Cattle, dogs, small ruminants and wild ruminants are the species most commonly affected, while in cats, horses, and pigs, it is less frequently reported. Although babesiosis has been observed worldwide, porcine babesiosis remains an uncommon disease, with a very limited number of cases reported. Here, we describe a case in a 12-year old pot-bellied pig from South Africa that died after a history of anorexia and reluctance to rise for two days. A complete necropsy, blood smear cytology, reverse line blot (RLB) hybridization and 18S rRNA sequencing were performed. Numerous Babesia spp. hemoparasites and a moderate regenerative anemia were identified on blood smear, and a urine dipstick test yielded 4+ heme. Diffuse icterus and splenomegaly were observed upon gross examination. Histopathology revealed hemoglobin casts within renal tubules and collecting ducts, pulmonary edema, splenic congestion, and intrahepatic cholestasis. BLASTN homology of the 18SrRNA sequence revealed a 100% identity to the published sequence of Babesia sp. Suis isolated from pigs in Italy. This case of babesiosis in a pig highlights the clinical manifestations and gross and pathological findings of porcine babesiosis.